Pengaruh Penerapan Pembelajaran Berbasis Artificial Intelligence (AI) terhadap Peningkatan Literasi Siswa SMP - Lukman Lukman; Herwandi Sape; Habiba Ulfahyana (ITEKES Permata Ilmu Maros, 2025)
This study aims to analyze the effect of implementing Artificial Intelligence (AI)-based learning on the improvement of literacy skills among eighth-grade students at SMP PGRI, Maros Regency, in the Indonesian language subject. The research employed a quantitative approach with an experimental method using a one-group pretest–posttest design. The research population consisted of all eighth-grade students, who were entirely included as the sample through a total sampling technique, totaling 32 students (17 females and 15 males). The research instrument was a literacy skills test administered before and after the AI-based learning intervention. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, a paired sample t-test, and normalized gain (N-Gain) analysis. The results indicated a significant increase in students’ literacy scores from pretest to posttest. The normality test results confirmed that the data were normally distributed, thus meeting the assumptions for parametric analysis. The paired sample t-test revealed a significance value of p < 0.05, indicating a statistically significant effect of AI-based learning on students’ literacy skills. Furthermore, the N-Gain value fell within the moderate to high category, demonstrating the effectiveness of AI-based learning in optimizing the improvement of students’ literacy skills. It can be concluded that AI-based learning is effective in enhancing junior secondary school students’ literacy skills and has strong potential as an innovative instructional strategy to support educational transformation in the digital era.